A Critical Review of the Actualization of the Right to Control by the State Doctrine in the Policy on Revocation of Forest Area Permits/Concessions - Totok Dwi Diantoro (Jurnal Pembangunan Hukum Indonesia, 2025)
The Right to Control by the State (Hak Menguasai Negara or HMN) is a doctrine derived from Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia, which asserts that the land, water, and natural resources contained therein shall be controlled by the state for the greatest benefit of the people. In its decision, the Constitutional Court explained that the phrase "controlled by the state" reflects political democracy, whereby citizens entrust their sovereignty to the government in the management of natural resources.In exercising its authority, the government issued the Decree of the Minister of Environment and Forestry No. 01/2022 concerning the Revocation of Forest Area Concession Permits. This decree raised issues regarding the boundaries of authority between the forestry and land regimes. The purpose of this study is to examine how the doctrine of HMN is implemented in Decree No. 01/2022.This research employs a normative legal approach, analyzing the text of laws and regulations, court decisions, and legal doctrines. The findings reveal that, aside from the fact that Decree No. 01/2022 does not genuinely revoke problematic forest area permits, its administrative function (bestuurdaad) remains far from definitive and final. From the perspective of policy function (beleid), the decree even intervenes in the management of former forest areas, thereby exceeding its jurisdiction. However, even with this intervention, there is no evident concrete commitment to prioritize the interests of the people.The conclusion drawn from this study is that Decree No. 01/2022, as a manifestation of the HMN doctrine, still falls short of being oriented toward the greatest prosperity of the people.